Consumer co-creation of hybrid meat products: A cross-country European survey. (September 2022) - Grasso, Simona; Asioli, Daniele; Smith, Rachel
Highlights: Hybrid meat product formulations were investigated using consumer co-creation. Beef burgers with 25–50% plant-based ingredients and nutrition claims were preferred. Most consumers in the UK, Spain and Denmark were willing to try hybrid meat products. Hybrid meat products were considered more similar to plant-based products than meat. Hybrid meat products were seen as healthy, ethical and environmentally friendly. Abstract: Hybrid meat products are blends of meat and plant-based ingredients that could bridge the gap for consumers who want to reduce their meat intake, without sacrificing the taste, convenience and familiarity of traditional processed meat products. However, little is known about consumers' preferred formulations, willingness to try (WTT), willingness to buy (WTB), and how they are perceived compared to meat products and plant-based meat-free alternatives. Therefore, this study aimed to: 1) identify hybrid recipes with the most potential for acceptance using a co-creation approach; 2) understand WTT and WTB for hybrid products and 3) compare hybrid meat products vs meat products and plant-based meat-free alternatives on several attributes (healthy, ethical, environmentally friendly, convenient, affordable, tasty, enjoyable, acceptable, aspirational, nutritious, simple, safe). The online survey with a total of 2, 405 consumers in Denmark, Spain and the UK, revealed that across countries consumers prefer a hypothetical beef burger made with 25% or 50% plant-based ingredients (onions, herbs, spices, garlic and mushrooms) and with a nutritional claim on protein or fat. At least 57% of consumers were willing to try and at least 46% were willing to buy hybrid meat products. Across countries and for most attributes, hybrid meat products scored similarly to plant-based meat-free alternatives and differently from meat products. Hybrid meat products and plant-based meat-free alternatives were considered as healthy, ethical and environmentally friendly, while meat products were considered affordable, tasty, enjoyable and simple. These findings provide insights and practical suggestions for companies manufacturing innovative solutions for meat products and policy makers aiming to promote more varied diets.